Alternative Terms with Different Numbers of Constituents - Mitkevičienė, Asta (Verbum, 2024)
The paper deals with alternative denominations of concepts (synonymous terms, as well as terms and their abbreviations) with varying numbers of constituents, in order to determine the nature of the synonymy of such units and the linguistic mechanisms that underlie the alternatives. These mechanisms are distinguished according to the opposition of synonyms, hypothetically bi-directional processes being perceived in one opposition. The analysis considers whether synonymous terms with different numbers of constituents express the same number of concept characteristics and whether these characteristics overlap.On the basis of data from two Lithuanian terminological dictionaries, the following linguistic mechanisms of synonymy of terms with different number of contituents are identified: derivational compression vs. decompression, lexical reduction vs. lexical addition, lexical extending vs. lexical reduction (with transformation), abreviation vs. decompression, (non-)descriptive substitution, aspectual substitution and substitution by a sign of another language. Some of them lead only to formal differences between synonyms, others to semantic differences.
Keywords: term; synonyms; lexeme; abbreviation; concept characteristic